Geographical Evaluation for Irrigation Projects and its Effects on Agricultural Facts: Hydrological study - Abbas, Aram Dawood (Al-Adab Journal, 2021)
The irrigation projects in Halabja city are one of the vital agricultural projects. That contains three huge projects with its (45) branches in three areas (townships). (%90) of these depends upon fountain and springs to irrigate a land area about (26340) Acres, design capacity estimated by (230039153 m3/year), and about (73706512 m3/year) as it is. This study will focus on the specifications of designed water discharge and the reality, Also the specification of geographical locations of the projects while the agricultural investments for the projects seizes on the overall water amounts of the project. Accreditation has been done on the systemic and regional curriculum, which focuses on studying natural geographical factors and the humanitarian ones in determining the efficiency of the irrigation projects and how it is affected within the geographical location and creating a relationship between discharge amounts, agricultural lands, and orchards that could be irrigated. And to investigate advantages and disadvantages of the natural and humanitarian factors and how it is affects the projects in order to create future plans for the crisis to facilitate expanding the land areas. The study found many results which are descending the yearly water discharge average to the project in order to invest (%32) of the project efficiency, and that’s because of the land surfaces and terrains, the absence of future plans to irrigate bigger areas. The misuse of the irrigation water of the project by the farmers spatially and temporally. Also, there is a misuse in water drainage that estimated as (12284m3/year) for each acre and that is more than ten times the estimated water for each acre in case you plant any agricultural crop.